Fiscal federalism in Spain : The decentralisation: an unfinished work - Suarez Pandiello, Javier (1999)
I am going to destine this paper to critically summarise this process [decentralising] and the current situation about this. To do it, I will divide the work in four parts. First, I will briefly describe the general characteristics of the administrative Spanish system and I will try to remark which have been, in my opinion, the main determinants of the administrative and fiscal decentralisation process produced in Spain and its political and economic explanations.